A Prologue to (Re)2naissance - German, Ismail; Gezerman, Ahmet Ozan (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Having observed that modern mathematical theories of matter have begun to experience difficulties, a visit to their origins is made. The so-called Hermes revealed theory of matter has been explored. A theory of matter made up of infinitely hard, extremely tiny classical particles moving at the speed of light is proposed, and preliminaries of such a theory are investigated. Elementary particles are proposed to be handled as ordered bundles in a random vacuum, oscillating either simultaneously, 180 degrees out of phase, or as a mixture. This is proposed to be done under the restriction that phase and basic incremental motion is supposed to be quantized. The coincidence between the teachings of Hermes and the holy books, especially the Quran, has been brought to surface. The necessity of further research, which is urgent under current conditions, performed with the help of supercomputers at hand has been proposed.